2018
DOI: 10.1111/joic.12510
|View full text |Cite
|
Sign up to set email alerts
|

Three‐months optical coherence tomography analysis of a biodegradable polymer, sirolimus‐eluting stent

Abstract: The Orsiro® sirolimus-eluting stent with biodegradable polymer shows early vascular healing with a high rate of strut coverage at 3-month follow-up. OCT guided stent implantation had a positive impact on early vascular healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(33 reference statements)
0
8
0
2
Order By: Relevance
“…На различных моделях животных и в клинических исследованиях [39][40][41] было продемонстрировано, что СЛП с сиролимусом уменьшает утолщение неоинтимы по сравнению с ГМС и стентами, покрытыми полимерами. При этом происходит раннее эффективное созревание клеток неоэндотелия [42,43], на 25% снижается риск тромбоза стента по сравнению с другими СЛП нового поколения [44].…”
Section: развитие технологии коронарного стентированияunclassified
“…На различных моделях животных и в клинических исследованиях [39][40][41] было продемонстрировано, что СЛП с сиролимусом уменьшает утолщение неоинтимы по сравнению с ГМС и стентами, покрытыми полимерами. При этом происходит раннее эффективное созревание клеток неоэндотелия [42,43], на 25% снижается риск тромбоза стента по сравнению с другими СЛП нового поколения [44].…”
Section: развитие технологии коронарного стентированияunclassified
“…The technological advances of R-onyx DES provide the unmet needs of intracranial stenting, and the thin strut thickness remains a crucial characteristic in stent platform, demonstrating better device conformability, easier navigability, and lesser strut malapposition. Also, thin struts are associated with low levels of inflammation at the lesion site resulting in rapid and almost complete arterial re-endothelialization and reduced neointimal growth (29). Furthermore, the slim 2-mm stent enables stenting of a small target vessel diameter which is associated with a high incidence of vessel injury, difficult accessibility, and higher rates of ISR.…”
Section: -Month Angiogram (9 Patients)mentioning
confidence: 99%
“…In the most recent European randomized trials, this stent demonstrated a very good safety and efficacy profile. Indeed, its low rate of stent thrombosis reached the non-inferiority statistical significance compared to Xience Prime stent (Abbott Inc., United States)[ 18 - 19 ] with a faster strut endothelium coverage evaluated by optical coherence tomography in respect to the competitors[ 20 ]. These results could be achieved even after overcoming the major intrinsic structural limitation to the stent’s design, such as longitudinal shortening[ 21 ].…”
Section: Stent Engineering Considerationsmentioning
confidence: 99%